Covid-19 Corpse Burial Training - Petrus, Asan; Marbun, Doaris Ingrid; Harianja, Dessy (Talenta Publisher, 2022)
Since the first outbreak of Covid-19 disease in March 2020 until now, the pandemic has been occuring for almost two years and the number of cases are still increasing without signs of ending while the number of cases has almost reached four million cases (3,950,304 cases as of 19 August 2021). While transmission of Covid-19 is still increasing in Indonesia, reasons apart from the lack of implementation of health protocols also causes increase in number of cases, such as community activities that cause overcrowding, the forced retrieval of Covid-19 corpses from hospitals and the handling of corpses and mistakes in burial process is suspected to be one of the factors in the transmission of Covid-19 in the community that cannot be controlled. In order to anticipate a spike in cases of deaths due to COVID-19 and the possibility of dying at home or dying outside the hospital, training on the management of relocation and burial of COVID-19 bodies will be carried out in collaboration with the Medan city government. The target groups for the training on the management of curing and burial of COVID-19 bodies are BABINSA, BHABINKAMTIBMAS, sub-district employees and PUSKESMAS employees in the city of Medan with an estimated number of participants around 167 people divided into three sessions starting from August 24, 2021 to August 26, 2021. The objectives of this community service program are (1) to improve the skills of health care officers throughout the city of Medan in managing the handling of COVID-19 corpses. (2) improve the skills of health care officers throughout the city of Medan in the management of COVID-19 funerals. (3) anticipating the surge in deaths of COVID-19 cases so that they can still be handled according to the protocol for handling COVID-19 bodies. The method of carrying out the activity is the lecture and question and answer method which is then followed by a technical workshop / Management of Beginning and burial of COVID-19 bodies. Which will be held on 24-26 August 2021 at 14.00 WIB until finished.